Diagnosis of Academic Stress in University Students (Docentes 2.0 Journal, 2022)
Stress has become a matter of interest for researchers because its effects have repercussions on the academic performance of students, being able to cause anguish, anxiety, psychological disorders, and family and even social disorders. The main objective of this research was to determine the level of academic stress in the students of the Early Childhood Education Career of the Peninsula de Santa Elena State University, academic period 2021-2. The research was based on the deductive, positivist paradigm with a quantitative approach, descriptive-exploratory type, non-experimental design, and transversal cut. The sample consisted of 30 students between 18 and 22 years of age. The data collection technique used was a survey using a questionnaire of semi-structured questions to determine the level of academic stress of the students. The instrument's reliability was measured through Cronbach's coefficient, determining a value of 0.841. The most relevant results indicate a significant level of academic stress in university students accompanied by physical-psychological symptomatology manifested in alterations in sleep cycles, headache, muscle tension, anxiety, and irritability. Conclusion: as students advance in their studies, the level of stress increases; however, they have better management of symptoms due to the practice of recreational activities and adequate organization of time.
Keywords: Academic stress; students; university; diagnosis